2002
DOI: 10.1007/s00464-002-8848-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyester (Parietex) mesh for total extraperitoneal laparoscopic inguinal hernia repair

Abstract: Polypropylene mesh is the most commonly used mesh for open and laparoscopic hernia repair in the United States. A variety of newly developed polyester mesh products have recently become available. This is the first U.S. multiinstitutional study evaluating the initial experience of polyester mesh use for total extraperitoneal (TEP) laparoscopic inguinal hernia repair. Between January 2000 and June 2001, 337 patients underwent 495 TEP laparoscopic inguinal hernia repairs using polyester mesh. There were 309 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 14 publications
1
36
0
2
Order By: Relevance
“…Thus, newer-generation mesh products have been developed with lower tensile strength (N/cm) and more compliance than previous mesh products [17,18]. Our study provides data regarding intra-abdominal pressure during various activities that the newer mesh products need to protect against.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, newer-generation mesh products have been developed with lower tensile strength (N/cm) and more compliance than previous mesh products [17,18]. Our study provides data regarding intra-abdominal pressure during various activities that the newer mesh products need to protect against.…”
Section: Discussionmentioning
confidence: 84%
“…A multicentric study in Europe with this mesh yielded favorable results [19]. Ramshaw et al [24] reported the initial experience in the United States with the composite mesh and concluded that there are technical and long-term advantages to the use of this mesh for laparoscopic inguinal hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested by several investigators that many of the current mesh materials used for hernia repair restrict normal abdominal wall mobility because they are actually much stronger and stiffer than needed for an adequate repair [21]. Second-and thirdgeneration prosthetic biomaterials have been developed, which are intentionally less dense (g/cm 2 ) with less tensile strength (N/cm) than standard, nonabsorbable mesh, and which are more compliant with abdominal wall motion and more resistant to contraction due to reduced inflammation and good tissue ingrowth [5,22]. These novel biomaterials may provide adequate strength and improved postoperative function; however, little information is available regarding long-term outcomes after implantation.…”
Section: Discussionmentioning
confidence: 99%